Evaluasi Jenis Tanaman Biofilter Terhadap Pertumbuhan Ikan Nila (Oreochromis niloticus ) Dengan Menggunakan Sistem Akuaponik - Atihuta, Billiam; Rahim, Nurfitri; Risfany, Risfany (Jurnal Akuakultur Sungai dan Danau, 2025)
Tilapia (Oreochromis niloticus) cultivation is one of the important activities in the aquaculture sector that can be carried out using an aquaponic system, which is one of the integrated systems where fish farming waste in the form of metabolic residues and feed residues are used as fertiliser for plants. This study aims to identify the most effective plant types as biofilters in dual recirculation aquaponics systems and analyse the influence of plant biofilters on water quality and tilapia growth. The research method used a Complete Random Design (RAL) using four treatments and three repeats, namely P1 (control), P2 (mint plant), P3 (pakcoy plant), P4 (lettuce plant), then further testing was carried out using Analysis of Variance (ANOVA). The study parameters included absolute weight (BM), absolute length (PM), specific establishment rate (SGR), survival rate (SR), and water quality. The results showed that the use of aquaponic systems in tilapia rearing with lettuce, pakcoy, mint plant treatment and control had no real effect (P>0.05) on absolute weight growth, absolute length increase and specific growth rate (SGR), but had a real effect (p< 0.05) on tilapia survival rate.